Action Research for Graduate Program Improvements: A Response to Curriculum Mapping and Review - Jacobsen, Michele; Eaton, Sarah Elaine; Brown, Barb; Simmons, Marlon; McDermott, Mairi (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
There is a global trend toward improving programs and student experiences in higher education through curriculum review and mapping of degree programs. This paper describes an action research approach to program improvement for a course-based MEd degree. The driver for continual program improvement came from actions and recommendations that arose from an institutionally mandated, year-long, faculty led curriculum review of professional graduate programs in education. Study findings reveal instructors’ perceptions about how they enacted the recommendations for program improvement, including (1) developing a visual conceptualization of the program; (2) improved connections between the courses; (3) articulation of coherence in goals and expectations for students and instructors; (4) an increased focus on action research; (5) increased ethics support and scaffolding for students; and (6) the fostering of communities of practice. Study findings highlight strengths of the current program and course designs, action items, and research needed for continual program improvement.